Guillain-Barré syndrome: causes, immunopathogenic mechanisms and treatment (2016)
Introduction: Guillain-Barré syndrome is a rare disease representing the most frequent cause of acute flaccid symmetrical weakness of the limbs and areflexia usually reaching its peak within a month. The etiology and pathogenesis remain largely enigmatic and the syndrome results in death or severe disability in 9–17% of cases despite immunotherapy. Areas covered: In terms of etiology, Guillain-Barré syndrome is linked to Campylobacter infection but less than 0.1% of infections result in the syndrome. In terms of pathogenesis, activated macrophages and T cells and serum antibodies against gangliosides are observed but their significance is unclear. Expert commentary: Guillain-Barré syndrome is a heterogeneous condition with numerous subtypes and recent data point towards the role of ganglioside epitopes by immunohistochemical methods. Ultimately, the syndrome results from a permissive genetic background on which environmental factors, including infections, vaccination and the influence of aging, lead to disease. © 2016 Informa UK Limited, trading as Taylor and Francis Group.